Differences in Colorectal Cancer Awareness Between Vegetarians and Nonvegetarians: A National Cross-Sectional Study From Palestine - Mohamedraed Elshami; Maram Albandak; Mohammed Alser; Ibrahim Al-Slaibi; Mohammed Ayyad; Mohammad F. Dwikat; Shoruq A. Naji; Balqees M. Mohamad; Wejdan S. Isleem; Adela Shurrab; Bashar Yaghi; Yahya Ayyash Qabaja; et al. (JCO Global Oncology, 2024)
PURPOSETo compare colorectal cancer (CRC) awareness between vegetarians and nonvegetarians in Palestine.MATERIALS AND METHODSThe validated Bowel Cancer Awareness Measure and Cancer Awareness Measure-Mythical Causes Scale were translated into Arabic and used to assess awareness of CRC signs/symptoms, risk factors, and mythical causes. The total awareness score of each domain was calculated and categorized into tertiles; the top tertile was considered as good awareness. Multivariable logistic regression analysis was used to examine the association between being a vegetarian and displaying good awareness in each domain.RESULTSThis study included 4,623 participants: 560 vegetarians (12.1%) and 4,063 nonvegetarians (87.9%). Lump in the abdomen was the most recognized CRC sign/symptom among both nonvegetarians (n = 2,969, 73.1%) and vegetarians (n = 452, 80.7%). Vegetarians were less likely than nonvegetarians to display good awareness of CRC signs/symptoms (odds ratio, 0.59 [95% CI, 0.48 to 0.72]). Lack of physical activity was the most identified modifiable CRC risk factor in both nonvegetarians (n = 3,368, 82.9%) and vegetarians (n = 478, 85.4%). Similarly, having a bowel disease was the most identified nonmodifiable risk factor among both nonvegetarians (n = 2,889, 71.1%) and vegetarians (n = 431, 77.0%). There were no associated differences between both groups in the awareness levels of CRC risk factors. The most recognized food-related CRC causation myth in nonvegetarians was drinking from plastic bottles (n = 1,023, 25.2%), whereas it was eating burnt food in vegetarians (n = 176, 31.4%). Having a physical trauma was the most recognized food-unrelated myth in both nonvegetarians (n = 2,356, 58.0%) and vegetarians (n = 396, 70.7%). There were no associated differences in the awareness of CRC causation myths between both groups.CONCLUSIONAwareness of CRC was notably low in both Palestinian vegetarians and nonvegetarians. Particularly, vegetarians demonstrated lower awareness of CRC signs and symptoms.